2001
DOI: 10.1136/mp.54.5.307
|View full text |Cite
|
Sign up to set email alerts
|

IGF status is altered by tamoxifen in patients with breast cancer

Abstract: Tamoxifen increases IGF-BP3 and IGF-BP1 concentrations. It also decreases the IGF-1 to IGF-BP3 ratio but this effect may be limited after long term use. Longer follow up, with larger numbers of patients, should determine when, and for how long, tamoxifen can reduce circulating IGF-1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
2

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 19 publications
0
17
0
2
Order By: Relevance
“…Four other studies have examined the effect of soy on IGF status (unpublished observations, Wangen et al, 2000;Aukema and Housini, 2001;Woodside & Campbell, 2001;Khalil et al, 2002). In a rat model of polycystic kidney disease, soy protein feeding resulted in reduced IGF-1 in both normal and affected male animals (Aukema & Housini, 2001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Four other studies have examined the effect of soy on IGF status (unpublished observations, Wangen et al, 2000;Aukema and Housini, 2001;Woodside & Campbell, 2001;Khalil et al, 2002). In a rat model of polycystic kidney disease, soy protein feeding resulted in reduced IGF-1 in both normal and affected male animals (Aukema & Housini, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Tamoxifen has been shown to lower IGF-1 concentrations in breast cancer patients by up to 30% (Pollak et al, 1990;Campbell et al, 2001). Isoflavones are a class of phytoestrogens that may have a variety of potential health benefits in endocrine-responsive cancers and cardiovascular disease (Bingham et al, 1998;This et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…pegvisomant), IGF-IR antibodies and analogs of IGF-I (Khandwala et al 2000). Clinical studies have demonstrated the efficacy of the antiestrogen tamoxifen, which decreases the IGF-I/IGFBP-3 ratio via increased IGFBP-3 (Campbell et al 2001) and reduced IGF-I levels (Osborne 1998), in the treatment and prevention of breast cancer (Fisher et al 1998). Another estrogen receptor modulator, raloxifene (used for the treatment and prevention of osteoporosis in postmenopausal women) was shown to decrease the IGF-1/IGFBP-3 ratio and has been proposed for future studies in breast cancer prevention (Torrisi et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Treatment of breast cancer patients with the antiestrogens tamoxifen or raloxifene decreased the IGF-I/IGFBP-3 molar ratio such that lower amounts of circulating IGF-I were available for mitogenic signaling [122,123]. Somatostatin analogues also reduce IGF signaling by reducing IGF-I levels.…”
Section: Insulin-like Growth Factor-i-receptor-targeted Therapymentioning
confidence: 99%